Assessing the effects of online educational intervention on pharmaceutical promotions: a pre–post study among medical and pharmacy students in Pakistan - Gillani, Ali Hassan; Arshad, Hafsa; Yang, Caijun; Arshed, Muhammad; Atif, Naveel; Bashir, Kamran; Abbas Malik, Hafiz Muhammad; Fang, Yu (Frontiers in Pharmacology, 2025)
BackgroundPharmaceutical promotion tend to alter prescribing and dispensing behaviors pharma companies target undergraduate students. Teaching about such promotion is inadequate, and little research has been done in Pakistan regarding this issue. Therefore, we designed and implemented an online educational intervention on pharmaceutical promotion and evaluated its effect on the knowledge and attitude of medical and pharmacy students.MethodsAn online interventional study was conducted among pharmacy and medical students to evaluate their pre and post perception and attitude score using a questionnaire. The module was developed by information from the WHO/HAI module on pharmaceutical promotion. The pre–post median score was calculated for each item. Demographic variation in median score was evaluated by Mann–Whitney and Kruskal–Wallis tests, and total median scores before and after the module were compared using the Wilcoxon signed ranks test. We analyzed the data by using SPSS version 23.0 for Windows.ResultsThere is significant modification in most of the perception and attitude items of pharmacy and medical students (p < 0.001). There is also a significant decrease in the total perception, attitude, and median scores of the medical and pharmacy students (p < 0.001). In terms of demographic variations, female students tend to show lower perception and attitude scores in both the cohort. Medical students from private organizations showed lower pre and post scores than those from government medical schools.ConclusionThere is a significant decrease in inclination toward promotion after the module in medical and pharmacy students. It shows the effectiveness of online intervention provided to students. There should be teaching for healthcare students on how to choose and use independent information sources to assess pharmaceutical promotions.